Prevention of esophagopharyngeal reflux by augmenting the upper esophageal sphincter pressure barrier. (27th June 2014) - Shaker, Reza; Babaei, Arash; Naini, Sohrab R.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Incompetence of the upper esophageal sphincter (UES) is fundamental to the occurrence of esophagopharyngeal reflux (EPR), and development of supraesophageal manifestations of reflux disease (SERD). However, therapeutic approaches to SERD have not been directed to strengthening of the UES barrier function. Our aims were to demonstrate that EPR events can be experimentally induced in SERD patients and not in healthy controls, and ascertain if these events can be prevented by application of a modest external cricoid pressure. Study Design Individual case control study. Methods We studied 14 SERD patients (57 ± 13 years, 8 females) and 12 healthy controls (26 ± 3 years, 7 females) by concurrent intraesophageal slow infusion and pharyngoscopic and manometric technique without and with the application of a sustained predetermined cricoid pressure to induce, detect, and prevent EPR, respectively. Results Slow esophageal infusion (1 mL/s) of 60 mL of HCl resulted in a total of 16 objectively confirmed EPR events in none patients and none in healthy controls. All patients developed subjective sensation of regurgitation. Sustained cricoid pressure resulted in a significant UES pressure augmentation in all participants. During application of sustained cricoid pressure, slow intraesophageal infusion resulted in only one EPR event (P < .01). Conclusions Slow esophageal liquid infusion unmasks UES incompetence evidenced as the occurrence of EPR. Application of 20 to 30 mm Hg cricoid pressure significantly increases the UES intraluminal pressure and prevents pharyngeal reflux induced by esophageal slow liquid infusion. These techniques can be useful in diagnosis and management of UES incompetence in patients suffering from supraesophageal manifestations of reflux disease. Level of Evidence 3b Laryngoscope 124:2268–2274, 2014